A control volume scheme using compact integrated radial basis function stencils for solving the Richards equation - Duc Ngo-Cong; Nam Mai-Duy; Antille, Diogenes L.; van Genuchten, Martinus Th [UNESP] (Elsevier B.V., 2020)
A new control volume approach is developed based on compact integrated radial basis function (CIRBF) stencils for solution of the highly nonlinear Richards equation describing transient water flow in variably saturated soils. Unlike the conventional control volume method, which is regarded as second-order accurate, the proposed approach has high-order accuracy owing to the use of a compact integrated radial basis function approximation that enables improved flux predictions. The method is used to solve the Richards equation for transient flow in 1D homogeneous and heterogeneous soil profiles. Numerical results for different boundary conditions, initial conditions and soil types are shown to be in good agreement with Warrick's semi-analytical solution and simulations using the HYDRUS-1D software package. Results obtained with the proposed method were far less dependent upon the grid spacing than the HYDRUS-1D finite element solutions.
Keywords: Richards equation; Finite volume method; Integrated radial basis function; Compact stencil; Unsaturated flow